Psychosocial, emotional and behavioral problems, quality of life, and mental health care seeking behaviors among children and adolescents in Jordan: a national school-based survey - Khader, Yousef; Abu Khudair, Sara; Tanaka, Eizaburo; Kufoof, Lara; Al Nsour, Mohannad; Aqel, Ashraf; Maayeh, Mohammad; Kharabsha, Ahmad (Frontiers in Public Health, 2024)
ObjectivesThis study aimed to estimate the prevalence of psychosocial, emotional, and behavioral problems and their symptoms among children and adolescents in Jordan, assess their quality of life, and examine mental health help-seeking behavior.MethodsA large-scale school-based national survey was conducted in Jordan among children and adolescents aged 8 to 18 years (grades 3 to 12) from the host and refugee populations, utilizing a multi-stage stratified cluster sampling technique to select a nationally representative sample. Two versions of structured questionnaires were used: proxy parent version for students in grades 3 to 6 (8–11 years) and self-report version for students in grades 7 to 12 (12–18 years). The study questionnaires employed internationally recognized and validated tools in English, which were translated into Arabic.ResultsA total of 8,000 (3,433 (42.9%) boys, 4,567 (57.1%) girls) and (3,593 (44.9%) children, 4,407 (55.1%) adolescents) were included. About 24.5% of children had anxiety symptoms (18.0% of Jordanians, 34.5% of Syrian camp refugees, 33.7% of Syrian urban refugees, and 24.7% of Palestinian camp refugees) and 16.6% of children had major depressive disorder symptoms (11.0% of Jordanians, 25.4% of Syrian camp refugees, 25.0% of Syrian urban refugees, and 14.0% of Palestinian camp refugees). Almost 13.9% of children and 19.7% of adolescents had abnormal levels of total emotional and behavioral difficulties. Nearly 16.5% of children and 35.0% of adolescents had poor overall health-related quality of life. When experiencing a personal or emotional problem, only 28.1% of children’s parents would seek help for their children and 19.7% of adolescents would seek help for themselves.ConclusionThe study revealed a high prevalence of various mental health issues’ symptoms, particularly among refugees and female adolescents. Intention to seek help is relatively low, suggesting that children and adolescents’ mental health needs are not being widely met. It is crucial to implement integrated and coordinated plans and programs that effectively target multiple factors that impact children and adolescents’ mental health, while also respecting the prevailing cultural context. A key aspect of promoting the mental well-being of children and adolescents in Jordan is the inclusive involvement of refugees and individuals from other nationalities.